Risk Factors for Diabetic Nephropathy among Newly Detected Type 2 Diabetic Patients Attending a Tertiary Care Hospital of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Patients with type 2 diabetes mellitus may present with different macro- and micro-vascular complications including diabetic nephropathy. This study was designed to evaluate the risk factors for diabetic nephropathy among newly detected type 2 diabetic patients. Methods: This case-control study was done at BIRDEM General Hospital, Dhaka, Bangladesh from January to September 2017. Adult (³18 years), type 2 diabetic patients, who were detected as diabetic for the first time, within the previous three months and who tested, at least, 2 urine samples for urine albumin to creatinine ratio (UACR), at least 6 weeks apart, were consecutively enrolled for the study. Pregnant ladies, patients with diagnosed kidney disease, patients having features of glomerulonephritis and systemic diseases like vasculitis and systemic lupus erythematosus, history of recent fever, urinary tract infection and menstruation were excluded. Patients having UACR ³30 mg/g in at least 2 (out of 3, if tested) samples were taken as cases and those with UACR < 30 mg/g were controls. Data were analyzed by statistical package for social sciences (SPSS) version 20.Results: Total patients were 224 with female predominance (150, 67%). Fifty one (22.8%) patients had diabetic nephropathy (microalbuminuria = 47 and overt proteinuria = 4). Multivariate regression analysis revealed that, hypertension [odds ratio (OR) = 3.71; 95% CI 1.23 to 4.31, p = 0.003], smoking (OR = 3.27; 95% CI 2.91 to 4.79, p = 0.003), family history of diabetes (OR = 2.31; 95% CI 1.84 to 3.14, p = 0.005) and diabetic nephropathy (OR = 3.34; 95% CI 2.40 to 4.97, p = 0.001), dyslipidaemia (OR = 2.31; 95% CI 1.98 to 3.91, p = 0.023), increased body mass index (BMI) (OR = 2.11; 95% CI 1.54 to 4.87, p = 0.001 and high glycated haemoglobin (HbA1c) (OR 3.21; 95% CI 1.71 to 5.97, p = 0.034) were significant risk factors for diabetic nephropathy.Conclusion: One in every five type 2 diabetic patients had diabetic nephropathy during diabetes diagnosis and most patients had microalbuminuria. Hypertension, dyslipidaemia, smoking, family history of diabetes and diabetic nephropathy, increased BMI and high HbA1c were significant risk factors for diabetic nephropathy among newly detected type 2 diabetic patients.J Bangladesh Coll Phys Surg 2023; 41: 15-21